Which Industries Are Economically Relevant to the System? - Christian Schneemann; Enzo Weber; Marc Ingo Wolter; Gerd Zika (Wirtschaftsdienst)
Abstract With the economic shutdown in the wake of the COVID-19 pandemic, the importance of some industries for the national economy has come into focus. This report identifies industries that are closely linked with the rest of the economy through supply chains; stopping production in these industries would have a significant impact on the overall economy. On the one hand, there are industries in which production losses lead to massive demand losses in other industries. On the other hand, there are industries in which production downtimes lead to massive delivery difficulties for other industries. Beyond these interdependencies, we also account for negative effects stemming from the loss of income and from consumption or investment decisions.